Addressing the links among agriculture, malaria, and development in Africa - Asenso-Okyere, Kwadwo; Asante, Felix A.; Tarekegn, Jifar; Andam, Kwaw S. (International Food Policy Research Institute, 2011)
While most people can readily grasp malaria's impact on smallholder productivity and development, the impact of agriculture development on the disease is less understood. Many agricultural practices increase the spread of malaria; in order to truly combat the disease, the risks involved in these practices must be managed and effective policy initiatives must take into account the two-way linkages between malaria and agricultural development.